2016
DOI: 10.5812/ircmj.38743
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Road Traffic Injuries in Iran: Based on the Data from Disaster Management Information System (DMIS) Of the Iranian Red Crescent

Abstract: Background: Road traffic injuries (RTIs) are the leading cause of injuries and the second cause of mortality in Iran. Objectives: The aim of this study was to investigate the epidemiological pattern of RTIs in Iran based on the data from disaster management information system (DMIS) of the Iranian Red Crescent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…As the present research revealed, RTIs comprised 23.6% of total injuries among elderly people. Most studies showed these injuries to be the main reason of mortalities and morbidities when compared to the other types [ 53 - 58 ]. According to WHO, RTIs bears the burden of about 24% of accident mortalities by itself [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…As the present research revealed, RTIs comprised 23.6% of total injuries among elderly people. Most studies showed these injuries to be the main reason of mortalities and morbidities when compared to the other types [ 53 - 58 ]. According to WHO, RTIs bears the burden of about 24% of accident mortalities by itself [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kerman roads accommodate about 10,000,000 trips per year, but also have the highest rate of RTIs in Iran. It is reported that in 2016 alone, the RTIs in this province led to 13,624 injuries and 920 deaths [14], [16], [17], [18], [19]. Therefore, this province can be a suitable field for investigating the problem of vehicle fires and related causes, from both regional and international perspectives (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…With a population of about 80 million people, Iran is exposed to a wide range of natural and man-made hazards, such as earthquakes, drought, and traffic accidents (4,5). Among about 300 most populated cities of Iran, approximately, 77% of them are built on faults and seismic zones and 50% are prone to floods (6).…”
Section: Introductionmentioning
confidence: 99%